Effect of a modified regimen on drug-sensitive retreated pulmonary tuberculosis: A multicenter study in China - Ge, Qiping; Ma, Yan; Zhang, Lijie; Ma, Liping; Zhao, Caiyan; Chen, Yuhui; Huang, Xuerui; Shu, Wei; Chen, Shengyu; Wang, Fei; Li, Bo; Han, Xiqin; et al. (Frontiers in Public Health, 2023)
Objective: Retreatment pulmonary tuberculosis (PTB) still accounts for a large proportion of tuberculosis, and treatment outcome is unfavorable. Recurrence rate of retreatment PTB based on long-term follow up is not well demonstrated. This study aimed to evaluate the treatment effects of optimized re-treatment regimens, and explore recurrence of 56-month follow-up after treatment successes. Methods: We conducted ambispective cohort study in 29 hospitals from 23 regions of China and enrolled re-treatment PTB patients from July 1, 2009 to Dec 30, 2014, with follow-up until Dec 31, 2020. Patients were divided into two re-treatment regimen groups including standard and optimized group. Patients with successful treatment outcomes were followed up at least 56 months. We compared the effects of different regimens and the recurrence at different durations among re-treatment PTB. Results: A total of 381 bacterial positive re-treatment PTB were enrolled in the study; among them, 244 (64.0%) patients were in the optimized group and 137 (36.0%) in the standard group. Overall, the treatment success rate of optimized group was significantly higher than standard group (84.0% vs. 74.5%, P = 0.024); and the recurrence rate in optimized group was significantly lower than standard group (2.4% vs. 8.8%; P < 0.001). There was no significant difference in the incidence of adverse effects between the optimized and standard groups (25.8% vs. 21.2%, P = 0.547). Conclusion: Optimized retreatment regimen has better treatment effects including higher treatment success rate and lower recurrence rate, and no increase in adverse reactions compared with standard regimen in retreated drug-sensitive PTB patients.